Results of ZBB Exercise Undertaken by Planning Commission - Planning Commission (Planning Commission, 2002)
As a follow up of the Finance Minister’s Budget Speech for 2001-02 and in order to implement the decision of the National Development Council taken in its last meeting on 01.09.2001, which was chaired by the Prime Minister, the Planning Commission has undertaken a zero-based budgeting exercise
Planning Commission
Planning Commission